Common House Spider, Achaearanea tepidariorum (C. L. Koch) (Arachnida: Araneae: Theridiidae) - Glavis B. Edwards (EDIS, 2004)
The common house spider, Achaearanea tepidariorum (C.L. Koch), may be the most abundant of the several species of spiders that live in the company of man in the southeastern United States, especially in Florida. Although Archer (1947) thought that A. tepidariorum was less common inside houses than Pholcus phalangioides Fuesslin (Pholcidae) in Alabama, he also noted its abundance. This document is EENY-238 (originally published as DPI Entomology Circular 279), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2001.